Constructivism Explained Malaysia’s Ratification Withdrawal of International Convention on the Elimination of All Forms of Racial Discrimination (ICERD) in 2018 - Alen Tiara; Surwandono Surwandono (Journal of Islamic World and Politics, 2022)
Malaysia is one of two Muslim-majority countries in the world that have not ratified ICERD. ICERD is part of the Convention on Human Rights, which obliges each country to eliminate all forms of racial discrimination. After 61 years of Barisan Nasional (BN) in power, Malaysia won the concept of 'New Malaysia' under the new authority of Pakatan Harapan (PH) in the 14th election. PM Mahathir Mohamad followed up on 'New Malaysia' by conveying the discourse on ICERD ratification at the 73rd UN General Assembly. The discourse was canceled in November 2018 after massive resistance from the BN opposition and Muslim-Malay unity. The cancellation of ratification can be explained through constructivism regarding the interests of maintaining economic, social, and political security for Malay-Muslim, which is based on the identity of the Malayan leadership during state formation of Malaysia.